Penerapan Metode An-Nahdliyah Dalam Pemahaman Membaca Al-Qur’an Santri TPQ Miftahul Ulum Lamongan - Salamah, Ika; Sholeh , Muhammad Badrus; Afifah; Negoro, Rohmatullah Hadi (At-Tahfidz: Jurnal Ilmu Al-Qur'an dan Tafsir, 2025)
The ability to read the Qur'an properly and correctly is a fundamental skill that every Muslim must possess. However, in reality, many TPQ students are still not fluent, even after years of study. This condition indicates that the learning methods used are not yet fully effective in improving the ability to read the Qur'an. This study aims to analyse the application of the An-Nahdliyah method in teaching Qur'an reading at the Miftahul Ulum Lamongan TPQ. The study uses a descriptive qualitative approach, with data collected through observation, interviews, and documentation. Data analysis was conducted interactively through a process of reduction, presentation, and conclusion drawing, while data validity was tested using source and method triangulation. The results of the study indicate that the application of the An-Nahdliyah method, which emphasises talaqqi, musyafahah, and gradual repetition, has proven effective in improving students' ability to read the Qur'an in accordance with the rules of tajwid. In addition, this method also fosters discipline, independence, and love for the Qur'an. The successful application of this method is supported by teacher competence, community support, and the method's suitability to the pesantren tradition. However, obstacles such as limited learning time and facilities remain.